Oral health and the care of pregnant women: workshops as a strategy to problematize practices in basic health care in residents living in the peripheral areas of the hills in the city of Santos - NUNES NETO,Ricardo Antonio (2018)
ABSTRACT Objective: the aim of this study is to question Primary Health Care (PHC) concerning oral health during prenatal care in facilities of primary health care in the residents living in the hills peripheral areas of the city of Santos, São Paulo. Methods: Using a qualitative approach, workshops on PHC concerning oral health were held in three primary care units which present different forms of organization. The transcribed material was analyzed using thematic analysis. Results: the teams have been trying to organize dental agendas giving priority to pregnant women, however difficulties in monitoring attendance commitment have been found. Therefore the use of protocols and the approach to oral health theme during the educational groups have been used as strategies for improving treatment commitment. Regardless of the organization of the PHC unit, the teams have claimed the search for pregnant women care merely in acute painful situations as well as the fear of harming the fetus caused by dental treatment as the main cause of treatment dropout. Some professionals had doubts about the use of local anesthetics in pregnant women. Conclusions: The valorization of oral health care during prenatal care was not unanimous among the professionals and the use of the permanent education strategy applied in the services led the teams to carefully question their practice as well as search for practice integrality.